ANALYSIS OF THE RELATIONSHIP BETWEEN INTEREST AND LEARNING OUTCOMES OF PHYSICS IN SENIOR HIGH SCHOOL - BoangManalu, Eva Novrianti; Iqbal, Muhammad; Garcia, Colocia (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2024)
This research is research on the relationship between interest in physics and physics learning outcomes. The aim of this research is to find out how student interests relate to student learning outcomes at senior high school 8 Muaro Jambi. This type of research is quantitative research using correlational quantitative descriptive methods. The data collection technique in this research was to use a questionnaire and the questions were distributed to students with a sample of 60 people, namely class XI students at senior high school 8 Muaro Jambi. With a population of all senior high school Negeri 8 Muaro Jambi students. Data analysis in this research uses a quantitative type of research using the SPSS program to test assumptions (normality and linearity) and create hypotheses through correlational tests. The results of the research show that using the correlation test, the Pearson correlation value was 0.008 <0.05, so it can be stated that Ho is rejected or there is a relationship between the character of national spirit and student learning outcomes at senior high school Negeri 8 Muaro Jambi.